MiR-296-5p ameliorates deep venous thrombosis by inactivating S100A4. Issue 21 (November 2021) - Pan, Zhichang; Zhang, Yu; Li, Chuanyong; Yin, Yuan; Liu, Rui; Zheng, Guangfeng; Fan, Weijian; Zhang, Qiang; Song, Zhenyu; Guo, Ziyue; Rong, Jianjie; Shen, Yixin
Deep venous thrombosis is one of the most common venous thromboembolic diseases and has a low cure rate and a high postoperative recurrence rate. Furthermore, emerging evidence indicates that microRNAs are involved in deep venous thrombosis. miR-296-5p is an important microRNA that plays a critical role in various cellular functions, and S100A4 is closely related to vascular function. miR-296-5p is downregulated in deep venous thrombosis patients, and its predicted target S100A4 is upregulated in deep venous thrombosis patients. Therefore, it was hypothesized that miR-296-5p may play a vital role in the development of deep venous thrombosis by targeting S100A4. An Ox-LDL-stimulated HUVEC and deep venous thrombosis mouse model was employed to detect the biological functions of miR-296-5p and S100A4. Dual luciferase reporter assays and pull-down assays were used to authenticate the interaction between miR-296-5p and S100A4. ELISA and Western blotting were employed to detect the protein levels of thrombosis-related factors and the endothelial-to-mesenchymal transition (EndMT)-related factors. The miR-296-5p levels were reduced, while the S100A4 levels were enhanced in deep venous thrombosis patients, and the miR-296-5p levels were negatively correlated with the S100A4 levels in deep venous thrombosis patients. miR-296-5p suppressed S100A4 expression by targeting the 3ʹ UTR of S100A4. MiR-296-5p knockdown accelerated ox-LDL-induced HUVEC apoptosis, oxidative stress, thrombosis-related factor expression, and EndMT, while S100A4 knockdown antagonized these effects in ox-LDL-induced HUVECs. S100A4 knockdown reversed the effect induced by miR-296-5p knockdown. Moreover, the in vivo studies revealed that miR-296-5p knockdown in deep venous thrombosis mice exacerbated deep venous thrombosis formation, whereas S100A4 knockdown had the opposite effect. These results indicate that elevated miR-296-5p inhibits deep venous thrombosis formation by inhibiting S100A4 expression. Both miR-296-5p and S100A4 may be potential diagnostic markers and therapeutic targets for deep venous thrombosis.